1999
DOI: 10.1093/clipsy/6.2.204
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychological interventions on medical cost offset: a meta-analytic review

Abstract: The impact of psychological interventions on the use of medical services was evaluated by examining the outcome of 91 studies published between 1967 and 1997 using meta-analytic techniques and percentage estimates. Psychological treatments included various forms of psychotherapy, behavioral medicine, and psychiatric consultation. Patients included those undeqping medical procedures such as surgery, patients with a history of overutilization, and patients being treated only for psychological disorderr including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
3
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 11 publications
5
136
3
4
Order By: Relevance
“…While evidence-based psychological treatment outcome research provides robust data to support inclusion of such services within the evolving, integrated, interprofessional health care system, clinical outcomes that are cost effective and actually can contribute to cost savings in this accountable system will be expected and be beneficial to the field. Thus, continued collection of medical cost offset research data that supports psychological services (Chiles, Lambert, & Hatch, 1999;Tovian, 2004) should be built into routine program evaluation, be a core skill taught to the next generation of healthcare psychologists, and routinely reported in the literature, so that advocates for psychology can use that information in discussions with policy makers.…”
Section: Trendsmentioning
confidence: 99%
“…While evidence-based psychological treatment outcome research provides robust data to support inclusion of such services within the evolving, integrated, interprofessional health care system, clinical outcomes that are cost effective and actually can contribute to cost savings in this accountable system will be expected and be beneficial to the field. Thus, continued collection of medical cost offset research data that supports psychological services (Chiles, Lambert, & Hatch, 1999;Tovian, 2004) should be built into routine program evaluation, be a core skill taught to the next generation of healthcare psychologists, and routinely reported in the literature, so that advocates for psychology can use that information in discussions with policy makers.…”
Section: Trendsmentioning
confidence: 99%
“…Studies aimed at reducing costs using psychosocial interventions have also targeted patients presenting primarily with physical illness. A comprehensive meta-analysis of 91 medical cost offset studies in medical populations published between 1967 and 1997 concluded that 90% of the studies reported some degree of decreased medical utilization following psychological intervention [73]. The estimated savings were $1,759 USD per person over all of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…12 Treatable mental health conditions, particularly anxiety and depression, are common comorbidities of chronic illness in AYA 13 and are associated with poor health status 14 and greater cost compared to chronic illness without comorbid mental health conditions. 15 …”
Section: Problemmentioning
confidence: 99%
“…40,41 Psychological interventions for anxiety and depression are effective 42 and have been shown to decrease medical costs, with the largest effects demonstrated for treatment integrated with medical care. 15 Despite this, 66% of AYA with mental illness do not receive care. 43 Web-based cognitive behavioral therapy (CBT) is effective and feasible for treating mild-to-moderate anxiety and depression in young adults.…”
Section: Solutionmentioning
confidence: 99%